EDUKASI PEMERIKSAAN IVA PADA WANITA USIA SUBUR DI KELURAHAN BATUANG TABA NAN XX KECAMATAN LUBUK BEGALUNG KOTA PADANG - Miranie Safaringga; Desmawati Desmawati; Marzatia Yulika; Auwilla Marta Tasman; Novi Aulia Driza; Siti Aisyah; Asti Marian Sari; Kiran Nandini Fijri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Cervical cancer is the second leading cause of death due to cancer in women after breast cancer, especially in developing countries. The high morbidity and mortality rates of cervical cancer according to WHO are due to delays in treatment. This happens because of the delay in early detection of cancer and the lack of public knowledge about the symptoms of cervical cancer. Based on the results of a survey conducted at RW 1 Batuang Taba Village, Lubuk Begalung District, there were 71% of women of childbearing age who were sexually active, with 93% of them having never done early detection of cervical cancer either by IVA or Pap Smear methods. For this reason, it is necessary to revive public awareness to carry out early detection of cervical cancer, one of which is health education. Based on an analysis of the pretest and posttest questionnaires given to 12 women, the Wilcoxon test showed that the education provided had a significant effect on increasing women's knowledge (Z = -3.126, p = 0.002). The percentage of knowledge increased significantly from 58.3% to 83.3% after education. Apart from that, from the post-test questionnaire, it was also known that as many as 91.7% of women were interested in early detection of cervical cancer. This activity succeeded in increasing the knowledge and interest of women of childbearing age regarding early detection of cervical cancer so that it is hoped that it can increase the awareness of women of childbearing age to carry out early detection of cervical cancer every 5 years in women of childbearing age.